Psychological First Aid sebagai Pertolongan Pertama Korban Pasca Bencana: Sebuah Studi Naratif - Fitriyani, Nina; Anjaly, Syafna Maulidia (PT Hakhara Akademia Indonesia, 2023)
Individuals affected by a disaster or traumatic incident, whether survivors, witnesses or respondents to the event, may have to try to face new challenges after the event and this can result in the emergence of post-traumatic stress disorder, so it is important to take initial steps to find out about this by psychological first aid. This research aims to describe the use of psychological first aid as first aid for victims of natural disasters. The findings in this research are that psychological first aid is first aid for victims experiencing a disaster or other crisis by means of psychological discussion. The psychological first aid framework consists of safety, function, action and the implementation system consists of seeing, hearing and connecting. The goal itself is to provide safety and security, reduce stress reactions, calm and comfort and establish connections to other sources of help.